The effectiveness of intramedullary screw fixation using the herbert screw for fifth metatarsal stress fractures in high-level athletes - Morimoto, S.; Tomoya Iseki, T.; Morooka, T.; Yoshiya, S.; Tachibana, T.; Tanaka, J. (The American Journal of Sports Medicine, 2021)
Background: Intramedullary screw fixation is the most common operative procedure used for treatment of fifth metatarsal stress fractures in athletes. However, the optimal implant in intramedullary screw fixation is still being investigated.